THE POSITION AND EXAMINATION OF VILLAGE REGULATIONS IN THE INDONESIAN LEGAL REGULATION SYSTEM - Ananda, Adhe Ismail; Ma’ruf, Umar (UNISSULA, 2024)
The purpose of this research is to find out the position and testing of village regulations in the legal and regulatory system in Indonesia.When village regulations are studied in the perspective of the hierarchy of laws and regulations, they must refer to Law No. 12 of 2011 as amended by Law No. 15 of 2019 and Law No. 13 of 2022 concerning the Formation of Legislation (LcFL). However, in Article 7 paragraph (1) LcFL does not stipulate the existence of Village Regulations in the order of laws and regulations. This condition has implications for the unclear legal status and authority to review the village regulations themselves. Furthermore, the issuance of Law No. 6 of 2014 concerning Villages, the position and authority of villages is based on the principle of autonomy which directs the form of village independence including the authority to make policies on a locality scale in the form of village regulations. The research results show that although village regulations are not mentioned in the hierarchy of statutory regulations, village regulations can be said to be a further elaboration of higher statutory regulations. so that its existence is still recognized as a legal product, while testing village regulations is carried out using executive preview and executive review testing mechanisms. The executive preview and executive review mechanism is the authority of the Regent/Mayor which was born from the process of monitoring legal products in the village in a preventive and repressive manner.